A feasibility study of establishing "Lechonan sa Noveleta" at Brgy. Magdiwang, Noveleta, Cavite - Bunda, April Joy B., author; De Ocampo, Maila R., author; Alde, Aldrin A., author; Ventura, Elizabeth A., author (Rosario, Cavite : Cavite State University-CCAT Campus, 2009)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2009.
Includes bibliographical references and appendices.
In English text.
Keywords: Roasting (Cooking).; Feasibility study; Profitability of the business; Entrepreneurship